Unusual bone localization of sarcoidosis mimicking metastatic lesions - Hamdi, Besma; Ben Jemai, Emna; Attia, Monia; Khalfallah, Ikbel; Riahi, Hend; Berraies, Anissa; Ladeb, Mohamed Faouzi; Rameh, Soumaya; Hamzaoui, Agnes (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Sarcoidosis is a multisystem disease of unknown origin. Diagnosis remains challenging, based on organ site involvement, histological confirmation of non-caseating granuloma and an appropriate clinical syndrome. Granulomatous bone involvement is rare and may be ignored because it is usually asymptomatic. Vertebrae, ribs and skull localizations are rarely reported. We described an interesting case of a woman with chronic and multiorgan sarcoidosis with unusual bone localizations.